2015
DOI: 10.1007/s00261-015-0406-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a pocket-size ultrasound device with a premium ultrasound machine: diagnostic value and time required in bedside ultrasound examination

Abstract: The clinical utility of portable ultrasound machines is limited. There will be clinical roles for distinct clinical questions such as detection of ascites or pleural effusion when used by experienced examiners. However, sensitivity in detecting multiple pathologies is not comparable to high-end ultrasound machines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 13 publications
2
52
0
4
Order By: Relevance
“…IQ image quality, VISIQ US tablet system, iu22 high-end US system pre-hospital emergency medicine [16,17], showing their value in achieving a quick clinical assessment and save time. Other studies have used pocket-size ultrasound devices to supplement computed tomography or have compared the clinical value of portable ultrasound devices with that of high-end instruments for diagnostic evaluation [16][17][18]. However, to the best of our knowledge, our study is the first to assess the potential of tablet US machines during interventional procedures.…”
Section: Discussionmentioning
confidence: 99%
“…IQ image quality, VISIQ US tablet system, iu22 high-end US system pre-hospital emergency medicine [16,17], showing their value in achieving a quick clinical assessment and save time. Other studies have used pocket-size ultrasound devices to supplement computed tomography or have compared the clinical value of portable ultrasound devices with that of high-end instruments for diagnostic evaluation [16][17][18]. However, to the best of our knowledge, our study is the first to assess the potential of tablet US machines during interventional procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The POC sonography had similar accuracy to conventional ultrasound when evaluating a specific condition, such as the diagnosis of abdominal aortic aneurysm (AAA) or posttransplant liver evaluation . However, POC was less accurate than conventional in a general diagnostic setting for abdominal, thoracic, and cardiac sonography …”
mentioning
confidence: 99%
“…[12][13][14][15][16][17] A limited number of studies in high-income countries have evaluated the diagnostic performance of conventional relative to POC ultrasound. [19][20][21][22][23][24] The POC sonography had similar accuracy to conventional ultrasound when evaluating a specific condition, such as the diagnosis of abdominal aortic aneurysm (AAA) or posttransplant liver evaluation. [19][20][21] However, POC was less accurate than conventional in a general diagnostic setting for abdominal, thoracic, and cardiac sonography.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the quality of the current evidence was low [10] and larger clinical trials are needed. One study found that overall fewer diagnoses could be made with a handheld US device compared to using a high-end machine but it was sufficient for distinct pathology like ascites [11].…”
mentioning
confidence: 99%